A Pan-Canadian Data Resource for Monitoring Child Developmental Health: The Canadian Neighbourhoods Early Child Development (CanNECD) Database - Janus, Magdalena; Enns, Jennifer; Forer, Barry; Raos, Rob; Gaskin, Ashley; Webb, Simon; Duku, Eric; Brownell, Marni; Muhajarine, Nazeem; Guhn, Martin (International Journal of Population Data Science, 2018)
The Canadian Neighbourhoods Early Child Development (CanNECD) database is a unique resource for research on child developmental health and well-being within the socioeconomic and cultural context of Canadian neighbourhoods. This paper describes the CanNECD database and highlights its potential for advancing research at the intersection of child development, social determinants of health, and neighborhood effects. The CanNECD database contains Pan-Canadian population-level child developmental health data collected through regional implementation of the Early Development Instrument (EDI), geo-coded information on residential neighbourhoods covering all of Canada, and socioeconomic and demographic variables from the Canada Census and Income Taxfiler database. The data are de-identified but linkable across datasets through use of common numeric sequences. The nearly 800,000 records spanning 2003-2014 and representing all Canadian provinces and territories (with the exception of Nunavut) are compiled in a secure electronic collection system at the Offord Centre for Child Studies, McMaster University in Hamilton, Canada. Early studies using the EDI demonstrated its utility as a tool for assessing child developmental health at a population level, and its potential for both community-level and large-scale monitoring of child populations. Research using the CanNECD database is now examining to what extent social determinants and the steepness of the social gradients of developmental health differ between geographical jurisdictions and between different sub-populations. We are also working to identify outlier neighbourhoods in which EDI scores are substantially higher or lower than predicted by a neighbourhood’s demographic and socioeconomic characteristics, and exploring other potentially important determinants of children’s developmental health. Finally, we are examining the extent to which change-over-time in aggregate EDI scores vary geographically, and how well it coincides with changes in socioeconomic factors. Thus, the CanNECD database offers the opportunity for research that will inform national policies and strategies on child developmental health.